2021
DOI: 10.18632/aging.202604
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of glucosamine-phosphate N-acetyltransferase 1 in the development of lung adenocarcinoma

Abstract: Glucosamine-phosphate N-acetyltransferase 1 (GNPNAT1) is a key enzyme associated with glucose metabolism and uridine diphosphate-N-acetylglucosamine biosynthesis. Abnormal GNPNAT1 expression might be associated with carcinogenesis. We analyzed multiple lung adenocarcinoma (LUAD) gene expression databases and verified GNPNAT1 higher expression in LUAD tumor tissues than in normal tissues. Moreover, we analyzed the survival relationship between LUAD patients’ clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…NPAS2 was demonstrated to be a potential prognostic biomarker in colorectal and breast cancers [ 25 , 26 ], and facilitated cell survival in hepatocellular carcinoma through trans-activation of CDC25A [ 27 ]. Several studies had collectively indicated that GNPNAT1 was closely related to poor prognosis in lung adenocarcinoma [ 28 , 29 ], and MELTF can be considered as a prognostic marker in lung adenocarcinoma and gastric cancer [ 30 , 31 ]. In summary, many studies have shown that five genes, DKK1, CCL20, NPAS2, GNPNAT1 and MELTF, are engaged in the pathogenesis and progression of multiple tumors.…”
Section: Discussionmentioning
confidence: 99%
“…NPAS2 was demonstrated to be a potential prognostic biomarker in colorectal and breast cancers [ 25 , 26 ], and facilitated cell survival in hepatocellular carcinoma through trans-activation of CDC25A [ 27 ]. Several studies had collectively indicated that GNPNAT1 was closely related to poor prognosis in lung adenocarcinoma [ 28 , 29 ], and MELTF can be considered as a prognostic marker in lung adenocarcinoma and gastric cancer [ 30 , 31 ]. In summary, many studies have shown that five genes, DKK1, CCL20, NPAS2, GNPNAT1 and MELTF, are engaged in the pathogenesis and progression of multiple tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of GNPNAT1 gene coexpression network analysis indicated that GNPNAT1 might participate in cell cycle transition, cancer development and immune infiltration in LUAD. 11 The other two studies also reported a correlation between GNPNAT1 and immune infiltration, indicating the potential function of GNPNAT1 in immunomodulation and immunotherapy. 9,21 In this study, we analysed GNPNAT1 expression in NSCLC.…”
Section: Discussionmentioning
confidence: 89%
“…Several recent studies also reached consistent conclusions about GNPNAT1 in LUAD. [9][10][11][12] However, few studies have reported the function of GNPNAT1 in NSCLC or LUSC. In addition, GNPNAT1 represents the key molecule facilitating the enhanced therapeutic effects of Abraxane on NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PGM3 has been reported to be overexpressed in prostate carcinoma [ 135 ]. GNPNAT1 is overexpressed in lung adenocarcinoma patients, which correlates with unfavorable prognosis [ 136 ]. GNPNAT1 is increased in prostate cancer compared with normal tissue [ 137 ] but GNPNAT1 level decreases as tumors become castration-resistant, indicating stage-specific roles of HBP during prostate cancer progression [ 137 ].…”
Section: Signaling Pathways Regulate Hbp Enzymes Ogt and Ogamentioning
confidence: 99%